Przekształć do postaci sumy algebraicznej wyrażenie:
2(a+b)
3(x+2y-6)
-2(x+4-y+z)
x(2y-54)
x(2y-54)
x(2x² -x+7)
a(b+a-ab)

ZADANIE NR 2
Zapisz jak najprościej
2a(b-3)-2b(a-3)
a(a+b)+a(a-b)+b(b+a)+b(b-a)
5a(a-2)+2a(a+5)
3(a+2b-3c)-2(a-2c)+5(c-b)-(a+b)

PROSZE WAS O POMOC :(

3

Odpowiedzi

2010-03-02T09:37:44+01:00
2(a+b)=2a+2b

3(x+2y-6)=3x+6y-18
-2(x+4-y+z)=-2x-8-2z
x(2y-54)=2xy-54x
x(2x² -x+7)=2x^3-x^2+7x
a(b+a-ab)=ab+a^2-a^2b

ZADANIE NR 2
2a(b-3)-2b(a-3)=2ab-6a-2ab+6b=-6a+6b
a(a+b)+a(a-b)+b(b+a)+b(b-a)=a^2+ab+a^2-ab+b^2+ab+b^2-ab=2a^2+2b^2
5a(a-2)+2a(a+5)=5a^2-10a+2a^2+10a=7a^2
3(a+2b-3c)-2(a-2c)+5(c-b)-(a+b)=3a+6b-9c-2a+4c+5c-5b-a-b=0


4 3 4
2010-03-02T09:40:13+01:00
2(a + b) = 2a + 2b
3(x + 2y -6) = 3x + 6y - 18
-2(x + 4 - y + z) = -2x -8 + 2y -2z
x(2y - 54) = 2xy - 54x
x( 2y - 54) = 2xy - 54x
x( 2x kw - x + 7) = 2x do szścianu - x kwadrat + 7x
a( b + a + ab) = ab + a kwadrat + a kwadrat b
zad.2
2a(b-3)-2b(a-3)=2ab-6a-2ab-6b=-6a-6b
a kwadrat+ab+a kwadrat-ab+b kwadrat+ab+b kwadrat-ab=2a kwadrat+2b kwadrat
5a kwadrat-10a+2a kwadrat+10a=7a kwadrat
3a+6b-9c-2a+4c+5c-5b-a-b=0
1 5 1
2010-03-02T09:40:29+01:00
2(a+b)= 2a+2b
3(x+2y-6)= 3x+6y-18
-2(x+4-y+z)= -2x-8+2y-z
x(2y-54)=2xy-54x
x(2y-54)=2xy-54x
x(2x² -x+7)=2x³-x²+7x
a(b+a-ab)= ab+a²-a²b

ZADANIE NR 2
Zapisz jak najprościej
2a(b-3)-2b(a-3)=2ab-6a-2ab+3= -6a+3
a(a+b)+a(a-b)+b(b+a)+b(b-a)=a²+ab+a²-ab+b²+ab+b²-ab=2a²+2b²
5a(a-2)+2a(a+5)=5a²-10+2a²+10= 7a²
3(a+2b-3c)-2(a-2c)+5(c-b)-(a+b)=3a+6b-9c-2a+4c-+5c-5b-a-b=0
3 4 3